Knowledge management 2.0 : organizational models and enterprise strategies - Boughzala, Imed.; Dudezert, Aurelie, 1975- (Hershey, PA : Information Science Reference, 2012)
'This book provides an overview of theoretical and empirical research on knowledge management generation in the Web 2.0 age, highlighting knowledge management evolution with a global focus and investigating the impact knowledge management 2.0 has on business models, enterprise governance and strategies, human resources, and IT design, implementation, and appropriation in organizations'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Knowledge management